Pemberdayaan Peningkatan Sadar Wisata Pelabuhan Melalui Konsep Ekonomi Biru dan Orientasi Potensi Lokal - Nurul Jannah Lailatul Fitria (Kreativasi : Journal of Community Empowerment, 2023)
Indonesia's most potential is as a maritime country and is known as a maritime country. So that maritime, marine, beach and coastal development is used as superior tourism. As in Probolinggo City is an area that has a maritime area. Probolinggo City has Tanjung Copper Port and Mayangan Beach Fishing Port with superior potential for various marine and fishery products. organizing Empowerment to Increase Port Tourism Awareness in the Probolinggo City Port Complex with the Concept of Blue Economy and Oriented to Local Potential aimed at Probolinggo City students. So that as part of academics and the millennial generation, they are more sensitive to the environment, especially to the existence of local tourism and are active in recognizing the relevance of tourism development in the Probolinggo City Complex with the concept of blue economy and optimizing local potential. This activity was held in the form of empowerment with pre-test activities, lectures accompanied by discussions, post tests, and post-activity e-book distribution. It is known that initially many partners did not know and lacked information related to Port Tourism Awareness with the Concept of Blue Economy and Oriented to Local Potential changed after the activity was held. As a result, all partners understand Port Tourism Awareness with the Concept of Blue Economy and Oriented to Local Potential in the Probolinggo City Port Complex.